Analysis of the Influence of Investment and Labor on Poverty Levels Through the Growth of the Indonesian Manufacturing Industry - Balqis, Riqah; Syahnur, Sofyan; Ernawati, Ernawati (Heca Sentra Analitika, 2024)
This study aims to eradicate poverty by utilizing the manufacturing industrial sector, which cannot be separated from the influence of investment value and labor absorption. The analysis methods used are multiple linear regression and Vector Autoregression (VAR). The study employs quarterly secondary data from 1999 to 2022. The results of the analysis show that labor and investment partially have a significant and positive effect on the growth of the manufacturing industry. Moreover, by using a bivariate causality test, this study proves the existence of a two-way causal relationship between the economic growth of the manufacturing industry and poverty. Additionally, the study also analyzed the response of the independent variable to the dependent variable using Impulse Response (IRF) and Variance Decomposition (VD). It can be concluded that the economic growth of the manufacturing industry responds negatively to poverty, and poverty responds negatively to the economic growth of the manufacturing industry until both reach a balance. The contribution made by each variable in forming the value of that variable is different from one another. The implementation of good governance is highly expected in efforts to eradicate poverty in Indonesia, one of which is through increasing the economic growth of the manufacturing industry and then creating useful programs to increase investment and employment.